2009
DOI: 10.1039/b903831k
|View full text |Cite
|
Sign up to set email alerts
|

Rapid enrichment of biomolecules using simultaneous liquid and particulate dielectrophoresis

Abstract: Here we show that dielectrophoretic (DEP) liquid actuation can be used to dispense arrays of nanoliter-sized droplets loaded with biomolecules. Size-based enrichment of these biomolecules occurs rapidly and simultaneously with the droplet dispensing. The physical mechanism responsible for the effect is the positive DEP force directed toward the electrodes that is imposed by the non-uniform electric field during the very rapid DEP actuated flow before droplet formation. Experiments conducted with a suspension o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 21 publications
0
27
0
Order By: Relevance
“…Theoretically, DEP manipulation of nm- sized proteins is challenging since extremely high electric field gradients are required in order to generate DEP forces large enough to compete with molecular diffusion, electrokinetic and electrothermal forces. Regardless, nearly 20 groups have investigated protein DEP experimentally employing metal electrodes 8,10,11,30 , nanopipettes 31 , carbon nanotubes 32 , and in droplets 33 . For instance, Hölzel demonstrated single molecule DEP trapping 3 with eDEP 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Theoretically, DEP manipulation of nm- sized proteins is challenging since extremely high electric field gradients are required in order to generate DEP forces large enough to compete with molecular diffusion, electrokinetic and electrothermal forces. Regardless, nearly 20 groups have investigated protein DEP experimentally employing metal electrodes 8,10,11,30 , nanopipettes 31 , carbon nanotubes 32 , and in droplets 33 . For instance, Hölzel demonstrated single molecule DEP trapping 3 with eDEP 8 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the manipulation of proteins by DEP has recently been demonstrated. 14,[26][27][28][29][30][31] As anticipated, high field strengths and gradients are required while DEP under DC and AC conditions was reported. Interestingly, proteins with molecular weight smaller than 100 kDa were successfully accumulated on electrodes, 14,26 carbon nanotubes, 27 within droplets, 28 and using nanopipettes.…”
Section: Introductionmentioning
confidence: 99%
“…14,[26][27][28][29][30][31] As anticipated, high field strengths and gradients are required while DEP under DC and AC conditions was reported. Interestingly, proteins with molecular weight smaller than 100 kDa were successfully accumulated on electrodes, 14,26 carbon nanotubes, 27 within droplets, 28 and using nanopipettes. 19 H€ olzel et al showed the DEP induced trapping of the large multimeric protein R-phycoerythrin at metal electrode gaps; 30 whereas Bakewell et al investigated frequency dependent DEP behavior of avidin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, some research efforts turn to focus on developing techniques for maneuvering micro-/nano-sized particles. [20][21][22][23][24][25][26][27] However, only few of them are capable of harnessing particles programmably, i.e., addressable manipulation. Among the technologies, optoelectronic tweezers were first incorporated into a bead-based immunoassay for a surface-enhanced Raman scattering (SERS) detection.…”
Section: Introductionmentioning
confidence: 99%